About the Aesthetic Mystery in the Literary Text: Key Points for a Pedagogy of Literature (2016)
This article contemplates some implications of the concept aesthetic mystery , which, according to Roger Chartier, approaches elements that govern the production and reception of literary texts. To achieve this objective, we take into account reflections belonging to semiotics, literary theory, and philosophy of language. Subsequently, we incorporate these ideas into an analysis of the character Rebeca, in Cien años de soledad [ A Hundred Years of Solitude ], supported by methodical principles suggested by Barthes, who proposes that every single text must be analyzed in the light of a liberating theory of the signifier; and Larrosa, for whom literary reading installs a transformative experience of the imagination. The results show how the effort of demonstrating an aesthetic experience leads us to discover a complex web of meaningful associations that delay the capture of meaning, as well as suggest key points to continue enriching pedagogical reflections on the teaching of literature.